Impact of Heat Moisture Treatment and Pregelatinization of Corn Starch on the Functional and Nutritional Properties of Breads Supplemented with Corn Germ - Seyed Mohammad Hosseini; Maryam Amiri; Asiye Ahmadi-Dastgerdi; Maryam Zokaei (Journal of Food Quality)
Properties of modified starch are of great interest to the bakery industry. Moreover, corn germ incorporation in bread has multiple health benefits. The aim of this study was the formulation of Brotchen bread with corn germ flour (0, 10, 20, and 30% w/w) and modified corn starch (0, 10, 20, and 30% w/w). The effect of heat-moisture treatment (HMT) and pregelatinization (PG) of starch was investigated on the rheological and physicochemical properties of bread. The addition of corn germ flour and modified starch increased some farinograph properties, i.e., water absorption, consistency, and dough development time, and decreased dough stability. The degree of softening of the dough increased after 12 min after supplementation. The farinograph quality number in the dough containing HMT was the highest value. By replacing corn germ flour and modified starch, extensograph parameters such as dough resistance were strengthened and dough extensibility was weakened. Also, the energy of the dough increased. The highest fat, protein, fiber, and moisture content was observed in the treatment containing 30% corn germ flour and HMT starch (HMT3). Also, the HMT3 treatment had the highest specific volume and porosity and the lowest weight loss and hardness (p<0.05). Regarding the color parameters, HMT3 treatment showed the highest lightness (L∗) and the lowest yellowness (b∗). Enriched bread by corn germ had more iron, calcium, potassium, magnesium, and phosphorus compared to wheat bread. Regarding overall acceptability, no significant difference was observed between treated and untreated bread (p>0.05). Therefore, the corn germ flour and modified starch in the formulation of bread improved the functional and nutritional properties of bread and can be used in the bread formulation especially at a concentration of 30%.